Modelo de gestión logística para la empresa “ITAAV” del cantón la Maná, provincia de Cotopaxi. - Villarroel Ortiz, Gustavo Nicolai. (2019)
The chickens raising is a fundamental part for the economy of the country that also contributes to the feeding of the people, for this reason the research was carried out to propose an improvement to their warehousing and storage processes which in their majority are neglected by the farmers. The integrated poultry company “Avicola Villaroel” (ITAAV) located in Guayacan Town, Salento, La Maná, Cotopaxi, Ecuador, handles empirical processes in logistics management that differ from the technical models that exist today, which has not allowed to reach efficiency levels that contribute to be more competitive. For this, a logistic management model was defined according to the needs that contributes to the efficiency increase of the warehousing and storage processes of the company. For the research process, we used a qualitative-quantitative methodology that allowed us to obtain relevant data, in addition to performing an analysis and interpretation of the information obtained. It should be kept in mind that a field investigation was carried out that allowed obtaining data from the primary source that were real and consisted, for this the interview was used as a data collection technique and as an instrument of the interview guide, which allowed to obtain the necessary data to propose an adequate logistic management model for the situation of the company leaving aside the way in which the processes are handled and entering technical processes that will allow to increase the expected efficiency for internal and proprietary clients.